Enhanced red emission in perovskite light-emitting diodes via F-PEI additive - Yan Wen; Yi Shao; Xuanxuan Guan; Jihua Cao (AIP Advances)
Mixed halogen perovskite materials show good application potential in the field of light-emitting diodes. However, due to non-radiative recombination of defect states in perovskite films, the external quantum efficiency (EQE) and stability of perovskite light-emitting diodes (PeLEDs) still lag behind traditional LEDs. Herein, we modulated the perovskite crystallization process by adding fluorinated polyethylenimine (F-PEI) into the perovskite precursor solution, resulting in perovskite films with smaller grain sizes, smoother surfaces, and lower defect density. These improvements significantly improve the photoluminescence efficiency of perovskite films and the performance of corresponding diode devices, with the peak EQE of PeLEDs reaching 20.89% at 668 nm. In addition, the F-PEI additive improves the thermal stability of the device and extends the operating life of the device. This shows the potential of this additive to improve the performance of perovskite light-emitting diodes.